2018
DOI: 10.1007/s00384-018-2983-0
|View full text |Cite
|
Sign up to set email alerts
|

Fecal incontinence after transanal endoscopic microsurgery

Abstract: Fecal incontinence after TEM is more common than thought previously, resulting in significantly impaired quality of life. Older age at the time of operation was an independent risk factor for developing significant fecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The study concluded that TEM has significant rate of fecal incontinence that impairs quality of life. In comparison to laparoscopic low anterior resections which have reported Wexner scores of 5.2 ± 4.2 at 6 months postoperatively, and scores of 3.7 ± 3.4 at 12 months, the Wexner scores were similar for TEM [40] . TEM, however, still results in much lower fecal incontinence than open surgery which has reported Wexner scores as high as 14.2 at 6 months and 10.3 at 12 months after surgery [36] .…”
Section: Robotic Surgery For Rectal Cancermentioning
confidence: 62%
See 1 more Smart Citation
“…The study concluded that TEM has significant rate of fecal incontinence that impairs quality of life. In comparison to laparoscopic low anterior resections which have reported Wexner scores of 5.2 ± 4.2 at 6 months postoperatively, and scores of 3.7 ± 3.4 at 12 months, the Wexner scores were similar for TEM [40] . TEM, however, still results in much lower fecal incontinence than open surgery which has reported Wexner scores as high as 14.2 at 6 months and 10.3 at 12 months after surgery [36] .…”
Section: Robotic Surgery For Rectal Cancermentioning
confidence: 62%
“…They studied 93 patients who had undergone TEM for benign rectal lesions or T1N0 rectal cancer and found that the Wexner incontinence scale (range 0-10) was increased from baseline at 3 months, began to decline at 12 months and returned to baseline preoperative value at 60 months [39] . Another single center study was conducted in which a EuroQol (EQ-5D-5L) quality of life questionnaire and a Wexner fecal incontinence scale was given to 132 patients who underwent TEM for a variety of rectal lesions including adenocarcinoma with a median follow-up period of 96 months [40] . Those considered to have minor to no fecal incontinence were rated as having a Wexner score of 2 or less.…”
Section: Robotic Surgery For Rectal Cancermentioning
confidence: 99%
“…Lastly, the rate of late complications after ESD and TEM should be addressed. While transient anal pain and anal incontinence are somewhat benign and expected complications of TEM, 21,38 12.7% rate of rectal stricture in the ESD group might seem worrisome. However, in all those cases, the lesion resected occupied 90% or more of the rectal circumference.…”
Section: Discussionmentioning
confidence: 94%
“…Doornebosch et al [ 24 ] even concluded that TEM has no deteriorating effect on fecal continence in the short term (6 months). However, in a retrospective study of 132 patients who underwent TEM with a median follow-up of 96 months, 38 (28.8%) patients reported Wexner score of 3 or more, leading to their conclusion that fecal incontinence after TEM is relatively high, and it significantly impairs quality of life [ 25 ]. To our surprise, 3 (2.1%) patients reported a major LARS after TEM in our study, and their symptoms did not improve by 26, 39, 90 months respectively.…”
Section: Discussionmentioning
confidence: 99%